Berberine in Human Oncogenic Herpesvirus Infections and Their Linked Cancers - Šudomová, Miroslava; Berchová-Bímová, Kateřina; Marzocco, Stefania; Liskova, Alena; Kubatka, Peter; Hassan, Sherif T S (Viruses, 2021)
Human herpesviruses are known to induce a broad spectrum of diseases, ranging from common cold sores to cancer, and infections with some types of these viruses, known as human oncogenic herpesviruses (HOHVs), can cause cancer. Challenges with viral latency, recurrent infections, and drug resistance have generated the need for finding new drugs with the ability to overcome these barriers. Berberine (BBR), a naturally occurring alkaloid, is known for its multiple biological activities, including antiviral and anticancer effects. This paper comprehensively compiles all studies that have featured anti-HOHV properties of BBR along with promising preventive effects against the associated cancers. The mechanisms and pathways induced by BBR via targeting the herpesvirus life cycle and the pathogenesis of the linked malignancies are reviewed. Approaches to enhance the therapeutic efficacy of BBR and its use in clinical practice as an anti-herpesvirus drug are also discussed.
Keywords: herpetické infekce; Berberine; Kaposi’s sarcoma-associated herpesvirus; Herpesviridae Infections; klinické zkoušky jako téma; Inflammation; Neoplasms; replikace viru; latence viru; cancer; antivirové látky; berberine; oncogenic herpesviruses; zánět; Carcinogenesis; Animals; Antiviral Agents; lidé; berberin; Virus Latency; Virus Replication; Humans; Epstein–Barr virus; zvířata; karcinogeneze; inflammation; herpes simplex virus; myši; nádory; Herpesviridae; Mice; human cytomegalovirus; Clinical Trials as Topic